Liveworksheet Interactive E-Module Effect on Equal Fractions Comprehension at 4th Grade Elementary School - Firdaus, Fery Muhamad; Fadhilah, Nur; Wuryandari, Indriana Trisoma; Fadhli, Rahmat (Jurnal Prima Edukasia, 2024)
This study seeks to investigate the impact of utilizing the liveworksheet interactive e-module on the comprehension of equal fractions among fourth-grade pupils. This study employed a quantitative methodology, utilizing a quasi-experimental design. The research design employed is a posttest control only-control group design. The sample size for this study consisted of 26 children who were in the 4th grade at SDN 2 Kejambon. The investigation employed a simple random sampling technique. The instrument comprised six descriptive questions. The data analysis was conducted using a T-test as a prerequisite test, including normality and homogeneity tests, with the assistance of SPSS software. The results obtained from the T-test analysis include a t-value of 2.311 and a significance value (2-tailed) of 0.030, which is less than 0.05. The results obtained from the T-test investigation include a t-value of 2.311 and a significance value (2-tailed) of 0.030, which is less than 0.05. The liveworksheet interactive e-module was found to have an impact on the comprehension of the Equal fraction idea. Subsequently, invalid hypothesis (H0) that is "There is no significant difference in 4th grade student mathematic comprehension, both liveworksheet interactive e-module and video-based learning.", rejected. Whereas the first hypothesis (H1), that stated "There is significant difference in 4th grade student's mathematic comprehension, between liveworksheet interactive e-module and video-based learning", considered as valid.